2020
DOI: 10.1097/acm.0000000000002961
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Economies of Scale via Collaborative Interdisciplinary Global Health Tracks (CIGHTs): Lessons From Three Programs

Abstract: The authors would like to acknowledge and thank educators-in both global and local health care settings-who are committed to meaningful global health training for the next generation of physicians and other health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…GHST residents attributed their improvements to the program, which also revitalized the passion for medicine to a greater degree than other residency experiences. These results suggest that the GHST was effective in providing opportunities to engage and immerse residents in enriching global experiences, further supporting the value that experiential global health education programs impart on resident training as demonstrated by other institutions (Haq et al, 2019;Hau et al, 2017;Hernandez et al, 2016;Jalan et al, 2020;McHenry et al, 2020;Rybarczyk et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…GHST residents attributed their improvements to the program, which also revitalized the passion for medicine to a greater degree than other residency experiences. These results suggest that the GHST was effective in providing opportunities to engage and immerse residents in enriching global experiences, further supporting the value that experiential global health education programs impart on resident training as demonstrated by other institutions (Haq et al, 2019;Hau et al, 2017;Hernandez et al, 2016;Jalan et al, 2020;McHenry et al, 2020;Rybarczyk et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Medical schools, residency training programs, and fellowship programs have begun adding global health experiences and electives to their curricular offerings, and more residency programs now incorporate global health specialty tracks (Bills & Ahn, 2016;Haq et al, 2019;Jalan et al, 2020;Kolars et al, 2011;McHenry et al, 2020;Rybarczyk et al, 2020). In a systematic review of studies surveying US residency program directors, global health training was particularly prominent in three specialties: 83% of residency programs for preventive medicine, 74% of emergency medicine programs, and 71% of surgery programs included global health training.…”
Section: Introductionmentioning
confidence: 99%
“…), these curriculums are seemingly differentiated in their educational approach with our focus being on learning global health ethics especially through simulation whereas other programs have emphasized participation in bidirectional educational exchanges and public health courses. 32 Although it can be difficult to meet the needs of many different trainees, we have found that creating an educational space for global health trainees and mentors of all specialties is fundamental to a supportive and collaborative learning environment. By establishing a codified set of basic knowledge, attitudes, and professional skills rooted in ethical practice in STEGH, we can begin to prevent unintentional harms, improve patient and trainee safety, support and enable professional development for dedicated trainees and standardize best practices in clinical global health both within our institution and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…), these curriculums are seemingly differentiated in their educational approach with our focus being on learning global health ethics especially through simulation whereas other programs have emphasized participation in bidirectional educational exchanges and public health courses. 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation